Determination of Zinc in Lubricating Oil by Flame MS Employing Ultrasonic Extraction - Sabio, Rafael Miguel [UNESP]; Oliveira, Silvana Ruella [UNESP]; Tognolli, Joao Olimpio [UNESP]; Gomes Neto, José Anchieta [UNESP] (Perkin-elmer Corp, 2011)
The determination of zinc in lubricating oils by line-source flame atomic absorption spectrometry (LS-FAAS) is proposed employing an alternative sample preparation procedure based on ultrasonic wave-assisted acid extraction. The chemometric optimization of the main parameters influencing the extraction provided the following conditions: 1.3 mL of HCl, 5.0 mL of H(2)O(2), 120 seconds sonication time, 60 degrees C heating temperature, and 45% sonication amplitude of the ultrasound probe. Analytical curves in the 0.5 - 4.0 mg L(-1) Zn range were consistently obtained (R = 0.9990). Commercial unused lubricating oil samples were analyzed by the proposed method and by high-resolution continuum source flame AAS (HR-CS FAAS) as the comparative technique. A paired t-test showed that the results between the two techniques were in agreement at the 95% confidence level. The accuracy of the proposed method was evaluated using an alternative sample preparation method based on recovery tests. Recoveries in the 92 - 119% interval were found. The relative standard deviation was 4% and the limit of detection was 17.6 mu g L(-1).